Peran DPRD Sumatera Utara dalam Mengakomodasi Aspirasi Warga Terkait Sengketa Tanah untuk Peningkatan Kesejahteraan - Zai, Yarisman; Siallagan, Haposan (Universitas Pahlawan Tuanku Tambusai, 2025)
Land disputes are one of the crucial problems often faced by people in North Sumatra, especially related to land ownership and utilization which have a direct impact on the welfare of residents. The Regional People's Representative Council (DPRD) of North Sumatra has an important role in accommodating community aspirations related to this issue, both through legislative, budgetary, and supervisory functions. This study aims to analyze how the DPRD of North Sumatra plays a role in resolving land disputes and its impact on improving community welfare. Using a descriptive qualitative approach, data were collected through in-depth interviews with DPRD members, community representatives, and related institutions. The results of the study indicate that the DPRD of North Sumatra plays an active role in facilitating dialogue between residents and the government and other stakeholders. However, there are several challenges faced, such as the complexity of agrarian law and weak coordination between institutions, which need to be addressed to optimize the role of the DPRD in improving community welfare. Recommendations for this study include strengthening the role of the DPRD in advocating for community rights and increasing synergy between the DPRD and related institutions in handling land disputes.